Studi Kasus Keterlambatan Perkembangan Bahasa Anak Usia Dini 5-6 Tahun Di TK IT Abizar Al Hafiz - Sahri Wulandari; Sri Wahyuni; Faqih Hakim Hasibuan (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2024)
This research aims to find out how language development is delayed in children and the factors that hinder language development and support language development in children aged 5-6 years at Abizar Al Hafiz IT Kindergarten. This research uses a qualitative approach research methodology with a case study approach. This approach is carried out holistically, by explaining phenomena through words and language. The location of this research is at the Abizar Al Hafiz IT Kindergarten which is located in Terutung Payung Hilir Village, Bambel District, Southeast Aceh Regency. The time of this research is from July 2024 to August 2024, the data source in this research is the subject, there are 2 students and the object of this research is observing the language development of children who experience delays in children at the Abizar Al Hafiz IT Kindergarten. As well as teachers and parents of children who live in that place. The researcher's data collection process used observation, interviews and documentation. The results of the research revealed that young children with delays in language development find it difficult to communicate and mingle with other people, are less responsive when asked to communicate, pronounce words that are unclear or unclear, and have a very limited vocabulary. As well as factors that have the potential to cause delays in language development in children, namely the lack of children who are always given gadgets, the absence of peers to play with, the use of languages ​​other than Indonesian, the child's health history, and the lack of parental presence in the child's life.